08 Psycho-pedagogical training as means of personality harmonization of the future teacher - Halyna MESHKO (Association of Social and Educational Innovation, 2016)
The features of the psycho-pedagogical training are revealed in the article, its role in personality harmonization of the future teacher, warning of the professional stress, prevention of the "emotional burning out". Experience of training practice providing is described with future teachers. The content meaning of the psycho-pedagogical training, form and methods of its realization are described.